1979
DOI: 10.1038/bjc.1979.101
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes and macrophages in malignant melanoma IV. Effects of C. parvum on monocyte function

Abstract: Assays for the capacity of peripheral-blood monocytes (a) to mature in vitro into macrophages, (b) to reduce nitro-blue tetrazolium (NBT) and (c) to lyse antibody-coated human Group A red cells, were applied to a group of 82 patients with histologically proven malignant melanoma. In patients with micrometastatic disease there was an enhancement of red-cell lysis and NBT reduction, suggesting that their monocytes are in some way "activated", whereas NBT reduction was suppressed in those with overt dissemination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Leukocyte populations other than the lymphocyte have been monitored for indication of disease relapse or disease progression in serial immunological studies. In that regard, Hedley et al reported that monocyte maturation to macrophages in vitro and nitroblue tetrazolium dye (NBT) reduction by peripheral blood monocytes were diminished prior to or coincident with clinically detectable recurrence of melanoma [24]. Also, the value of serial leukocyte determinations need not be limited to post-surgical settings.…”
mentioning
confidence: 99%
“…Leukocyte populations other than the lymphocyte have been monitored for indication of disease relapse or disease progression in serial immunological studies. In that regard, Hedley et al reported that monocyte maturation to macrophages in vitro and nitroblue tetrazolium dye (NBT) reduction by peripheral blood monocytes were diminished prior to or coincident with clinically detectable recurrence of melanoma [24]. Also, the value of serial leukocyte determinations need not be limited to post-surgical settings.…”
mentioning
confidence: 99%
“…Considered in conjunction with the acute suppression and recovery in lymphocyte function, the increased monocyte numbers after 7 days suggest that one rational schedule for CP therapy might be infusions at 1-2-weekly intervals, rather than the monthly schedule which is currently widely used clinically. This suggestion would require confirmation by further studies, but Hedley et al (1979) have recently published data on monocyte function which also suggest that administration more often than every 4 weeks may be more appropriate in humans. These workers also demonstrated increased monocyte function using small intradermal doses of CP.…”
Section: Resultsmentioning
confidence: 99%
“…One patient who received intrapleural BCG as an adjunct to surgery showed a dramatic increase in maturation from 5% preoperatively to 31.5% 2 months postoperatively. This is of particular interest in view of the dramatic increases in monocyte maturation noted in patients with malignant melanoma after C. parvum treatment (Hedley et al, 1979). The correlation of depression of monocyte maturation with extent of disease raises the question whether increasing metabolic disturbance and general debility underlie the abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte production from marrow in animals is increased (Meuret et al, 1977) but recent reports suggest that the ability of monocytes to mature into macrophages in vitro is reduced (Currie & Hedley, 1977;Taylor & Currie, 1979). This lack of ability to mature has been shown to be related to prognosis in primary breast cancer (Taylor & Currie, 1979) and to be restored by treatment with Corynebacteriurn parvurn in patients with malignant melanoma (Hedley et al, 1979).…”
mentioning
confidence: 99%